The devil in the corner: A mixed‐methods study of metaphor use by those with spinal cord injury‐specific neuropathic pain. Issue 4 (6th October 2016) - Hearn, Jasmine Heath; Finlay, Katherine Anne; Fine, Philip A.
Abstract : Objectives: Metaphorical expressions of persistent pain play an influential role in the modulation of pain. This may be particularly distressing for those with physical disabilities such as spinal cord injury (SCI). Neuropathic pain (NP) after SCI is often described using metaphorical expressions such as burning and electricity. This study explored the use of metaphors by those with NP after SCI. Design: A qualitative, semi‐structured interview design was employed. Methods: Data were analysed using content analysis (CA) and interpretative phenomenological analysis to explore prevalence of metaphor use and its meaning. Sixteen individuals aged between 23 and 82 years, with chronic NP (persisting for 3 months or longer), arising from SCI were interviewed in their homes or on hospital wards ( M = 10, F = 6). Interviews lasted between 40 and 120 min. Results: The results capture a range of metaphorical expressions embedded in participants' accounts. Three themes emerged: (1) pain as a personal attack, (2) the desire to be understood, and (3) conveying distress without adequate terminology. CA revealed that younger age, female gender, and outpatient status were associated with increased metaphor use. Conclusions: This study highlights the power of metaphor in eliciting understanding of NP after SCI from others, whilst demonstrating the challenge of communicating NP. Cognitive treatment that incorporates image‐based techniques with acceptance and mindfulness‐based therapies may encourage adaptive responses to, and interpretation of, pain. This may subsequently reduce pain‐related distress and catastrophizing. Statement of contribution What is already known on this subject? Neuropathic pain is often described with metaphorical language such as burning and crushing. For those with physical limitations, metaphor use may induce or exacerbate psychological distress. However, for those with spinal cord injuries, metaphor use has received little attention. What does this study add? Metaphor use is common in those with spinal cord injury, with differences across gender and age. Core metaphors used conceptualized pain as an attacker or likened pain to heat and burning. Such language may have benefits in terms of improved understanding and increased empathy, but may be reflective of catastrophic thinking.